The Influence of Social Media Influencers on the Purchase Intention of Fashion Products for Generation Z on the Instagram Application - Fakhriah; Sularsih Anggarawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted to analyze and demonstrate the influence of a social media influencer, consisting of the variables of source credibility, source attractiveness, agreement with the product, and meaning transfer, on the purchase intention of fashion products for Generation Z on the Instagram application. The population in this study is Generation Z in Bengkulu province. The sample in this study consisted of 210 respondents who met the research criteria. The technique used in this study is purposive sampling technique. Multiple linear regression, t-test and coefficient (R-squared) test were used in this study. The research results show that: Source credibility, source appeal, product agreement and meaning transfer have a positive and significant impact on purchase intention for Generation Z fashion products on Instagram application.